Effect of different fertilizer doses and spacing on performance of Pearl Millet (Pennisetum glaucum L.) under Tripura Agro-Climatic Condition - Giri, U.; Lodh, P.; Thangjam, B.; Paul, N.; Awasthi, D. P.; Sangappa; Das, S.; Sen, D.; K.S., Th. Irenaeus; Debbarma, D.; Sarkar, A. (International Journal of Environment, Agriculture and Biotechnology, 2024)
A field experiment was conducted to study the effect of fertilizer and spacing on performance of Pearl Millet under Tripura agro-climatic condition during pre-kharif season in 2024 at the Experimental Farm of College of Agriculture, Tripura Lembucherra(23o56' N latitude and 91o10' E longitude, 160 m.s.l.) in a sandy loam soil with 12 treatment combinations (fourfertilizer level in main plot and three level of spacingin sub-plot) in a split plot design replicated thrice.Recommended Dose of Fertilizer (RDF) is 80:40:40 kg ha-1 as N: P2O5: K2O. The main plot treatments are F1: RDF 100%, F2: RDF 75%, F3: RDF 125%, F4: RDF 150%. The sub-plot treatments were S1: 30 cm X 20 cm, S2: 45 cm X 20 cm, S3: 60 cm X 20 cm. The study revealed that both the levels of fertilizer and spacing significantly influenced almost all the growth parameters, yield attributing characters, thegrain yield(kg ha-1) and stover yield (kg ha-1). The highest values of growth parameters, yield attributing characters, thegrain yield (kg ha-1) and stover yield (kg ha-1) were recorded when fertilizer applied @ 125% RDF (F3) in combination with spacing of 45cm x 20 cm (S2).